Transformasi Peran Akuntan dalam Era Revolusi Industri 4.0 dan Tantangan Era Society 5.0 - Rosmida Rosmida (Politeknik Negeri Bengkalis, 2019)
This research is titled transformation of the role of accountants in the era of the industrial revolution 4.0 and the challenges of the era of society 5.0. This study aims to determine the transformation of the role of accountants in the era of the industrial revolution 4.0 and the challenges that accountants will face in the era of society 5.0. This research is descriptive research. The conclusion is drawn based on a collection of opinions of experts, both experts in accounting and experts in the field of information technology. Based on the results of research and discussion that has been done it can be concluded that accountants must have a strategy to face the challenges of the accounting revolution. strategies that can be done, such as making sure you have certification, making goal orientation, making time management, always up to date, and using software to maximize performance. To face the challenges of the era of Society 5.0, accountants need to do the following five things: invest in developing digital skills, apply prototypes of new technologies, while learning by doing, education based on international certifycation, responsive to changes in industry, business and technological development, and curriculum and human-digital skills based learning (for educational institutions).